Inadvertent C2–C3 Union After C1–C2 Posterior Fusion in Adults - Takeuchi, Kazunari (Springer-Verlag, 2005)
Introduction: Some authors pointed out that there were more than a few patients with inadvertent C2–C3 union after C1–C2 posterior fusion, although few detailed studies of C2–C3 union have been reported. The purpose of this study was to clarify whether C2–C3 union accelerated adjacent C3–C4 disc degeneration after C1–C2 posterior fusion and to investigate the related factors for C2–C3 union. Methods: Sixteen patients with rheumatoid arthritis (RA group) (4 males, 12 females, mean age 60 years, mean follow-up period 4 years and 3 months) and fifteen patients without RA (non-RA group) (11 males, 4 females, mean 52 years, mean follow-up period 3 years and 10 months) who underwent C1–C2 posterior fusion were radiologically assessed. The C2–C3 union was defined as trabecular bone formation at C2–C3 interlamina in lateral radiograph. C3–C4 disc height was measured to evaluate the disc degeneration. Results: C2–C3 union rate was 56% and 60% in RA group and non-RA group, respectively. In RA group, postoperative C3–C4 disc height was lower (Student’s t-test, P = 0.029) and the decrease rate of C3–C4 disc height was higher (Student’s t-test, P = 0.015) in patients with C2–C3 union than in patients without C2–C3 union. In non-RA group, the age at operation was older (Student’s t-test, P = 0.0007), and the C1–C2 fusion angle (Student’s t-test, P = 0.012) was smaller in patients with C2–C3 union than in patients without C2–C3 union. Conclusions: C2–C3 union after C1–C2 posterior fusion occurred in more than half of both groups. Inadvertent C2–C3 union should be considered a radiological complication and a potential risk factor due to acceleration of C3–C4 disc degeneration in RA.